Topical Selenium Sulfide for the Treatment of Hyperkeratosis - Philip R. Cohen; Caesar A. Anderson (Adis, Springer Healthcare, 2018)
Abstract Hyperkeratosis presents as thickened skin. It can be congenital or acquired. Typically, it affects the palms and soles; the distribution of epidermal involvement is either diffuse, focal, or punctate. Microscopically, the pathologic signature of hyperkeratosis is marked orthokeratosis of the stratum corneum. Topical treatments provide the mainstay of therapy for hyperkeratosis. These include keratolytics (such as urea, salicylic acid, and lactic acid) and retinoids; physical debridement, topical corticosteroids, and phototherapy (using topical psoralen and ultraviolet A phototherapy) are other local therapeutic modalities. Selenium is a non-metallic essential element; its water-insoluble salt, selenium sulfide, is an active ingredient that is used (in either a foam, lotion, or shampoo) to treat not only seborrheic dermatitis but also tinea versicolor. Three individuals with hyperkeratosis involving their palms and/or soles are described; the hyperkeratosis was successful treated with topical selenium sulfide in either a 2.5% lotion/shampoo or a 2.75% foam. The response to topical selenium sulfide was not only rapid but also complete and sustained; none of the patients experienced any adverse events secondary to the therapy. In conclusion, we recommend that topical selenium sulfide be added to the therapeutic armamentarium for congenital or acquired hyperkeratosis-particularly for those patients with involvement of their palms and soles.